METODOLOGI PENDIDIKAN K.H AHMAD DAHLAN - Farikha, Lany (Fakultas Agama Islam Universitas Islam Madura, 2024)
In the context of educational methodology, Muslims are required to think and work hard in preparing and designing the vision, mission and strategy of the Islamic education system. One of the Muslim intellectual figures who worked hard to reconstruct the national education system was K. H. Ahmad Dahlan. In implementing education, K.H Ahmad Dahlan integrates religious and general education material in a curriculum similar to Dutch schools which is adapted to Islamic values. This research uses field research or interviews and documentation using a descriptive qualitative approach, namely a research process that produces data descriptive in the form of writing or expressions obtained directly from the field. The results of this research are; 1) The education designed by K.H Ahmad Dahlan has three main aspects, namely: moral and ethical education, individual education, and community education. Aims to create a generation that is intelligent and faithful, also responsive to the needs of society and the environment. 2) Applying learning methods that focus on practice, discussion, question and answer, and examples. 3) The concept of curriculum and methods of Islamic education in the modern era, which K.H Ahmad Dahlan initiated, is still very relevant. Islamic education is required to pay attention to Islamic moral, spiritual, and scientific values in integrating aspects of life.